Niechcący zrobiłam "Dark Souls" – gry wideo w instytucjach kultury z perspektywy twórcy i groznawcy - Bakun, Martyna (Replay. The Polish Journal of Game Studies, 2017)
Innovative technological solutions are becoming more and more popular in cultural institutions. Among such novelties as interactive exhibitions, specially designed applications, virtual tours, and augmented reality there is also a place for video games. This results in the emergence of new groups of game users, which leads to questions about the methods of designing this type of games. Based on her own experience and an analysis of the video game market, the author presents a strategy for designing video games that might be used in promoting cultural institutions. The important point in the analysis is designing engaging games for players usually uninterested in this medium. Elements taken into account include the use of commonly available design rules in the context of the discussed type of games, platform selection, choice of aesthetics, designing of mechanics, and testing.